Enhanced energy recovery in a microbial fuel cell and improved catalytic chromium (VI) reduction using biogenic palladium nanoparticles - Chirwa, Evans M.N. (University of Pretoria, 2024)
Dissertation (MEng (Water Utilisation Engineering) )--University of Pretoria, 2021.